Pegylated Nanoparticles for Brain Targeting- Opportunities and Challenges - Gupta, Utsav; Sultana, Shaheen (Current Nanomedicine, 2023)
As the blood-brain barrier (BBB) stops hazardous substances from entering the brain, creating treatment strategies to treat central nervous system (CNS) conditions is difficult. By circumventing the BBB, nanotechnology has emerged as a viable method for targeted medicine delivery to the brain. PEGylated nanoparticles (PEGNPs) have shown the ability to encapsulate a range of drugs and deliver them to the deepest regions of the brain. PEGNPs are a helpful tool in preclinical research for CNS diseases because of their extreme flexibility. Before PEGNPs can be employed in clinical practise, however, issues with their design and optimization for efficient brain targeting, as well as their long-term safety, must be resolved. Moreover, it is crucial to comprehend the basic principles of PEGNP trafficking through the BBB and how they affect CNS cells. Despite these difficulties, PEGNPs have the potential to completely alter the way CNS diseases are treated by allowing for precise medication delivery to the brain. This review emphasizes the potential and difficulties in using PEGNPs for brain targeting and describes current breakthroughs in PEGNP research for CNS diseases.
Keywords: Alzheimer’s